Salt-dome structures modeling in depth domain using ray tracing and seismic attribute analysis - Русаченко, Наталія; Пастушенко, Тетяна; Вижва, Сергій (Київський національний університет імені Тараса Шевченка, 2024)
Background. Increasing the resource base and hydrocarbon exploration is the main goal of performing seismic data acquisition. Due to the presence of salt diapirs, normal and reverse faults as well as other discontinuities in the geological subsurface, there appear characteristic features of seismic signals – a break in phase continuity and significant attenuation of the amplitude without a break in phase continuity. These geological features are sometimes distinguished by attenuation of the seismic signal or even an absence of wave field reflections. In areas of salt-dome tectonics, it is often completely impossible to trace any reflective horizons. To accurately map the fault location, deep or vertical horizons, it is necessary to improve the approach to obtaining and interpreting data in faulted areas with complex geology. Methods. The research presents an integrated approach to modeling the rays from each receiver of seismic signals to each bin on the reflective boundary. The reflected beams then propagate from the reflective boundary to the simulated position of the seismic receiver. Since the nature and velocity of beam propagation vary, it is possible to obtain additional information from zones shielded by faults or sub-vertical horizons, to trace the trajectories of seismic energy propagation and its focusing/defocusing zones. Verification of the seismic image and its geological content was performed using seismic attribute analysis. Results. Ray tracing allowed analyzing poor illumination zones below salt wings. During further steps such as processing and interpretation, ray tracing provided additional information for diapir mapping. Seismic attribute analysis was used as an additional tool to define the boundaries of the salt structure. This makes it possible to analyze the dynamic and kinematic parameters of the seismic field and map the salt body's boundaries based on these characteristics. Conclusions. An integrated approach involving several methods will solve the problem of mapping seismic horizons in areas surrounding fault zones with a weak seismic signal. A more reliable geological image can only be obtained by using complex sequences, including seismic processing, ray tracing, and seismic attribute analysis. The integrated application of the techniques demonstrates consistent geological results and has implications for discovering new deposits and hydrocarbon traps confined to the zones of development of salt-dome tectonics in the Dnipro-Donets basin.

Вступ. Збільшення ресурсної бази та видобутку вуглеводнів є основною метою сейсморозвідувальних робіт. У зв'язку з наявністю в геологічному середовищі соляних діапірів, розломів, скидів і підкидів з'являються характерні особливості сейсмічного сигналу – розрив суцільності фази і значне згасання амплітуди без розриву суцільності фаз. Іноді такі геологічні утворення ідентифікуються ослабленням сейсмічного сигналу або навіть відсутністю відбиттів у сейсмо-хвильовому полі. Часто на ділянках розвитку солянокупольної тектоніки взагалі неможливо простежити відбивальні горизонти. Для достовірного відображення місця розлому, крутопадаючих чи вертикальних контактів необхідно вдосконалити підхід до роботи з даними на ділянках з густою сіткою розломів і складною геологією. Методи. У дослідженні представлено комплексний підхід моделювання променів від кожного приймача сейсмічних сигналів до кожного біна на відбивальній границі. Потім відбиті промені поширювалися в геологічному середовищі від відбивальної границі до заданого положення сейсмічного приймача. Оскільки характер і швидкість їхнього поширення різні, то є можливість отримати додаткову інформацію із зон, екранованих розломами чи вертикальними контактами, дослідити траєкторії поширення сейсмічної енергії та зони її фокусування/дефокусування. Перевірка сейсмічного зображення та його геологічної змістовності була виконана за допомогою аналізу сейсмічних атрибутів. Результати. Трасування променів дало змогу проаналізувати зону поганого освітлення під соляними крилами. Під час подальших кроків, таких як обробка та інтерпретація, трасування променів надало додаткову інформацію для оконтурення діапіру. Як додатковий інструмент для визначення меж соляної структури використано аналіз сейсмічних атрибутів. Це сприяло аналізу динамічних і кінематичних параметрів сейсмічного поля та на основі цих характеристик картографуванню меж соляного тіла. Висновки. Комплексний підхід із залученням кількох методів допоможе розв'язати завдання простеження сейсмічних горизонтів на ділянках, що оточують зони розломів зі слабким сейсмічним сигналом. Достовірніше геологічне зображення можна отримати, лише використовуючи комплексні підходи, що передбачають не тільки сейсмічне оброблення, але й трасування променів, аналіз сейсмічних атрибутів. Комплексне застосування методик демонструє геологічно змістовні результати та створює передумови для відкриття нових родовищ і пасток вуглеводнів, які приурочені до зон розвитку солянокупольної тектоніки Дніпровсько-Донецької западини.
Моделювання соляно-купольних структур у глибинному домені з використанням трасування променів та аналізу сейсмічних атрибутів
Keywords: ray tracing; seismic data processing; seismic attribute analysis; interpretation; salt tectonics; diapir; hydrocarbons; oil; gas; трасування променів; оброблення сейсмічних даних; аналіз сейсмічних атрибутів; інтерпретація; соляна тектоніка; діапір